2020
DOI: 10.3389/fonc.2019.01515
|View full text |Cite
|
Sign up to set email alerts
|

CXCL1 as an Unfavorable Prognosis Factor Negatively Regulated by DACH1 in Non-small Cell Lung Cancer

Abstract: Background: Interaction between cancer cells with microenvironment is essential for cancer progression, therapeutic resistance and prognosis. Chemokine CXCL1 shows variable roles in the development of cancers. DACH1 has been considered as a tumor suppressor and represses the expressions of several chemokines. The relationship between CXCL1 and DACH1 in non-small cell lung cancer (SCLC) deserves further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 65 publications
3
29
0
Order By: Relevance
“…CXCL1 is also known as NAP-3, CINC-1, and GRO-α. This protein was originally identified in melanoma, and it was later confirmed to be expressed in neutrophils, macrophages, and epithelial cells and to be involved in inflammation, angiogenesis, and wound-healing biological processes [ 25 ]. Alzoghaibi et al [ 26 ] found that GRO-α levels were significantly higher in patients with IBD than in healthy controls, and that elevated GRO-α levels exacerbated IBD-related inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL1 is also known as NAP-3, CINC-1, and GRO-α. This protein was originally identified in melanoma, and it was later confirmed to be expressed in neutrophils, macrophages, and epithelial cells and to be involved in inflammation, angiogenesis, and wound-healing biological processes [ 25 ]. Alzoghaibi et al [ 26 ] found that GRO-α levels were significantly higher in patients with IBD than in healthy controls, and that elevated GRO-α levels exacerbated IBD-related inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In NSCLC, much attention has been paid to the functions of some CXC chemokines. For example, the CXCL1 paracrine network was identified to be linked with cancer chemoresistance and metastasis in 2012 [18], and in 2020, researchers found that CXCL1 was an unfavorable prognosis factor negatively regulated by DACH1 in NSCLC using immunohistochemistry staining [38]. In 2004, researchers found that COX-2 (cyclooxygenase-2) contributes to the progression of NSCLC tumorigenesis by enhancing the expression of angiogenic chemokines CXCL8 and CXCL5 [39], both of which can contribute to lung cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Here, consistently with a cancer-promoting role, its systemic concentrations were elevated. Moreover, ADMA levels positively correlated with immune mediators known to support cancer development, the most strongly with GROα (CXCL1), the cytokine released from tumors as well as tumor-associated macrophages and implicated in the recruitment of tumor-associated neutrophils [ 31 ] and promotion of metastasis [ 32 ], respectively, and associated with poor overall survival [ 33 ].…”
Section: Discussionmentioning
confidence: 99%